Impact of Oral Conditions and Subjective Factors on Academic Performance - Fernanda Ruffo Ortiz; Thiago Machado Ardenghi; Saul Martins Paiva; Marília Cunha Maroneze; Isabela Almeida Pordeus (Association of Support to Oral Health Research (APESB), 2021)
Objective: To evaluate the influence of oral health clinical and non-clinical indicators on adolescents' academic performance. Material and Methods: A longitudinal design was performed with a random sample of 1,134 12-year-old Brazilian adolescents. In 2012, the adolescents were clinically assessed by calibrated dentists and investigated about demographics, socioeconomic factors, dental service use, toothache, and verbal bullying related to oral condition via structured questionnaires. The contextual variable was obtained from the city's official database. After two years, 771 adolescents were reassessed. The outcome adolescent's academic performance (good or poor) was collected through official school's register. Multilevel logistic regression analyses were performed to assess associated factors for adolescents' academic performance. Results: Adolescents with toothache (OR 1.74; CI 95%: 1.05-2.89), who have been a victim of bullying (OR 2.23; CI 95%: 1.21-4.09), and were male (OR 1.92; CI 95%: 1.19-3.09) had a lower academic performance. On the other hand, adolescents whose mothers had higher educational levels (OR 1.79; CI 95%: 1.08-2.97) and belonged to higher-income households (OR 1.95; CI 95%: 1.18-3.23) had higher academic performance when compared to their peers. Conclusion: Adverse oral conditions, as well as subjective and socioeconomic factors, impacted on adolescents' academic performance.